Discourse analysis as a tool for understanding gender identity, representation, and equality - Mahtab, Nazmunnessa; Parker, Sara L. 1968-; Kabir, Farah 1960-; Haque, Tania; Sabur, Aditi; Sowad, Abu Saleh Mohammad (Information Science Reference, an imprint of IGI Global, 2016)
This book provides a thorough analysis of what language use and linguistic expression can teach us about gender identity in addition to current discussions on topics related to women's rights and gender inequality